2011
DOI: 10.1038/aps.2011.155
|View full text |Cite|
|
Sign up to set email alerts
|

Lipid metabolism disturbances and AMPK activation in prolonged propofol-sedated rabbits under mechanical ventilation

Abstract: Aim: To explore the mechanisms underlying the propofol infusion syndrome (PRIS), a potentially fatal complication during prolonged propofol infusion. Methods: Male rabbits under mechanical ventilation through endotracheal intubation were divided into 3 groups (n=6 for each) that were sedated with 1% propofol (Group P), isoflurane (Group I) or isoflurane while receiving 10% intralipid (Group II), respectively. Blood biochemical parameters were collected at 0, 6, 12, 18, 24, and 30-36 h after the initiation of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 21 publications
(38 reference statements)
1
8
0
Order By: Relevance
“…This time, rather than investigating how propofol induces the shedding of glycocalyx, we examined how a propofol overdose reduces its biosynthesis. Consistent with previous studies [ 5 , 39 ], we found that a propofol overdose significantly reduced endothelial ATP concentrations. Moreover, we found that a propofol overdose-induced ATP reduction was associated with a decrease in the production of endothelial proteoglycans.…”
Section: Resultssupporting
confidence: 93%
“…This time, rather than investigating how propofol induces the shedding of glycocalyx, we examined how a propofol overdose reduces its biosynthesis. Consistent with previous studies [ 5 , 39 ], we found that a propofol overdose significantly reduced endothelial ATP concentrations. Moreover, we found that a propofol overdose-induced ATP reduction was associated with a decrease in the production of endothelial proteoglycans.…”
Section: Resultssupporting
confidence: 93%
“…Furthermore, as was described above, propofol has calcium channel blocking properties on the heart, which lead to decreased cardiac performance [ 23 ] and promote inflammation in the cardiac muscle [ 24 ]. It is also possible that some patients who develop PRIS have a subclinical mitochondrial disorder [ 25 , 26 ].…”
Section: Pathophysiology Of Propofol Infusion Syndromementioning
confidence: 99%
“…The frozen samples were weighed and homogenized in ice-cold buffer. The sample protein concentration was determined with a BCA protein assay kit according to a previously described method [32] . The sample proteins were separated by 10% SDSpolyacrylamide gel electrophoresis (SDS-PAGE) and electrophoretically transferred onto a nitrocellulose membrane.…”
Section: Western Blotmentioning
confidence: 99%